Evaluation of energy input and greenhouse gases emissions from alfalfa production in the Sistan region, Iran. (November 2016) - Asgharipour, Mohammad Reza; Mousavinik, Seyed Mohsen; Enayat, Fatemeh Fartout
Abstract: The recognition of forage production methods that maximize energy efficiency and minimize Greenhouse Gases (GHGs) emissions is essential. The aims of this survey were to assess the energy consumption, emissions of GHGs and global warming potential (GWP) of alfalfa production systems in Sistan region, Sistan and Baluchestan province in the South–east of Iran. Data were collected randomly from 110 alfalfa farm using face-to-face questionnaire survey. Energy inputs included chemical fertilizers, diesel fuel, pesticides, seed, machinery and human labor. The results indicated that average total input and output energies in alfalfa production during the entire lifetime of the farm were 313.52 GJ ha − 1 and 962.85 GJ ha − 1, respectively. The most important energy inputs belonged to electricity (72.5%), followed by diesel fuel (12.3%) and N fertilizer (6.0%). Energy use efficiency and energy productivity were 3.07 and 0.209 kg MJ − 1, respectively. Share of direct and indirect energy were 85% and 15%, respectively. Total emissions of CO2, N2 O and CH4 in alfalfa farms were 8262.67 kg ha − 1, 557.31 kg ha − 1 and 7.65 kg ha − 1, respectively. Hence, total GWP was 181190 kg CO 2 e ha − 1 and 2.77 kg of CO 2 e kg − 1 of dry hay produced. In terms of CO2 e, 95.3% of the GWP originate from N2 O, 4.6% from CO2 and 0.1% from CH4 . Accordingly, efficient use of energy is essential to reduce the greenhouse gas emissions and environmental impact in alfalfa agroecosystems. Highlights: The total input energy was 313.52 GJ ha − 1 where the output was 962.85 GJ ha − 1 . Value of total GHGs emission was estimated at 181, 190 kg CO 2 e ha − 1 . The highest share of input energy in the production systems belonged to electricity. Alfalfa was fairly efficient in terms of energy consumption and GHGs emission. In terms of CO2 e, 95.3% of the GWP originate from N2 O, 4.6% from CO2 and 0.1% from CH4 .